Urgensi Persetujuan Anak sebagai Syarat Poligami (Perspektif Undang-Undang Perkawinan dan Hak Asasi Manusia - Rasyid, Muhammad; Arianti, Mega (Universitas Malikussaleh, 2021)
The concept of state law (rechtstaat) relating to corruption case has to be conducted by implementing law enforcement, law certainty, and justice.Â Any kind of policy in relation with corruption eradication has tobe done based on the application of legislation. Â The rule of legal officersÂ in eradicating corruption is highly influenced by integrity of morality and personal ethic (the maturnity of spiritual intelligence) by having good understanding on corruption eradication which is very significance in making decision in relation with corruptor.